Evaluación del uso de enzimas empleadas en el sistema rompedor de revoque para la degradación de polímeros presentes en el fluido de perforación Drill-in a escala laboratorio (2016)
It was evaluated the use of four enzymes in the formulation of a groundbreaking system cake generated by the drilling fluid DRILL-IN. This required form cakes underwent laboratory with breakers formulated with enzymes to see what the removal capacity each was. For the evaluation a brief description of the generalities of the drilling fluid DRILL-IN and breakers systems was performed. The fluid was prepared, the formation of cakes was simulated by filtering API was developed breakers, each with a different enzyme, and inits variation concentration, the other ingredients in the formulation of the breaker is left constant for the variation in results out product the enzymes used to degrade the polymers. Into a container containing the selected concentration breaker, were soaked plasters and thus formed was evaluated for each enzyme removal capacity which provided.